DEVELOPING CONTEXTUAL MATHEMATICS TEACHING MATERIALS USING KVISOFT FLIPBOOK TO ENHANCE MATHEMATICAL LITERACY - Aulyanissa Tsaqifa Maharshall; Nindiasari, Hepsi (Universitas Muhammadiyah Metro, 2026)
Students’ mathematical literacy is an essential competency that needs to be developed to address the challenges of 21st-century learning. However, the limited availability of engaging teaching materials that are relevant to real-life contexts remains a major obstacle in improving this ability. This study aims to develop technology-based mathematics teaching materials using Kvisoft Flipbook Maker with a contextual approach to support students’ mathematical literacy skills in number pattern material for eighth-grade students at SMPN 1 Bayah. This research employed the Research and Development (R&D) method using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The product developed is a flipbook-based mathematics teaching material that integrates indicators of mathematical literacy skills. The product validity test based on expert evaluations indicated that the developed teaching materials were highly valid, with validation scores of 89,16% from material experts, 92,5% from media experts, and 97,22% from education experts. The practicality test results showed that the product was highly practical, with a response rate of 99,44% from educators and 94,93% from students. Furthermore, the effectiveness test based on the N-Gain Score of 57,7% indicated that the product was moderately effective in improving students’ mathematical literacy skills. The findings demonstrate an improvement in students’ mathematical literacy before and after using the developed teaching materials. Therefore, the technology-based mathematics teaching materials developed using Kvisoft Flipbook Maker with a contextual approach are considered valid, practical, and sufficiently effective in supporting students’ mathematical literacy skills. Kemampuan literasi matematis peserta didik merupakan kompetensi penting yang perlu dikembangkan untuk menghadapi tantangan pembelajaran abad ke-21. Namun, keterbatasan bahan ajar yang menarik dan relevan dengan konteks kehidupan sehari-hari masih menjadi kendala dalam meningkatkan kemampuan tersebut. Penelitian ini bertujuan untuk mengembangkan bahan ajar matematika berbasis teknologi menggunakan Kvisoft Flipbook Maker dengan pendekatan kontekstual guna mendukung kemampuan literasi matematis peserta didik pada materi pola bilangan di kelas VIII SMPN 1 Bayah. Penelitian ini menggunakan metode Research and Development (R&D) dengan model ADDIE yang meliputi tahap Analysis, Design, Development, Implementation, dan Evaluation. Produk yang dihasilkan berupa bahan ajar matematika berbasis flipbook yang memuat indikator kemampuan literasi matematis. Hasil uji validitas produk berdasarkan penilaian para ahli menunjukkan bahwa bahan ajar yang dikembangkan berada pada kategori sangat valid, dengan persentase penilaian dari ahli materi sebesar 89,16%, ahli media 92,5%, dan ahli pendidikan 97,22%. Hasil uji kepraktisan menunjukkan bahwa produk termasuk kategori sangat praktis, dengan persentase respon pendidik sebesar 99,44% dan respon peserta didik 94,93%. Selanjutnya, hasil uji efektivitas berdasarkan N-Gain Score sebesar 57,7% menunjukkan bahwa produk berada pada kategori cukup efektif dalam meningkatkan kemampuan literasi matematis peserta didik. Hasil ini menunjukkan adanya peningkatan kemampuan literasi matematis sebelum dan sesudah penggunaan bahan ajar. Dengan demikian, bahan ajar matematika berbasis Kvisoft Flipbook Maker dengan pendekatan kontekstual dinyatakan layak, praktis, dan cukup efektif untuk mendukung peningkatan kemampuan literasi matematis peserta didik.